Characterization of sequence variability hotspots in Cranichideae plastomes (Orchidaceae, Orchidoideae) - Smidt, Eric de Camargo (PLoS One, 2020)
This study reports complete plastome sequences for six species of Neotropical Cranichideae and focuses on identification of the most variable regions (hotspots) in this group of orchids. These structure of these six plastomes is relatively conserved, exhibiting lengths ranging between 142,599 to 154,562 bp with 36.7% GC on average and exhibiting typical quadripartite arrangement (LSC, SSC and two IRs). Variation detected in the LSC/IR and SSC/IR junctions is explained by the loss of ndhF and ycf1 length variation. For the two genera of epiphytic clade in Spiranthinae, almost whole sets of the ndh-gene family were missing. Eight mutation hotspots were identified based on nucleotide diversity, sequence variability and parsimony-informative sites. Three of them (rps16-trnQ, trnT-trnL, rpl32-trnL) seem to be universal hotspots in the family, and the other five (trnG-trnR, trnR-atpA, trnP-psaJ, rpl32-infA, and rps15-ycf1) are described for the first time as orchid molecular hotspots. These regions have much more variation than all those used previously in phylogenetics of the group and offer useful plastid markers for phylogenetic, barcoding and population genetic studies. The use of whole plastomes or exclusive no-gap matrices also positioned with high support the holomycotrophic Rhizanthella among Orchidoideae plastomes in model-based analyses, showing the utility of plastomes for phylogenetic placement of this unusual genus.